Caracterización técnica y productiva del sistema bovino lechero de las ganaderías asociadas del cantón Bolívar de la provincia de Manabí - Pinargote Macías, Josselyn Alexandra (2020)
The purpose of the present investigation was the technical and productive characterization of the dairy cattle system in Bolívar canton, in order to carry out the information gathering of its current state. For this, a methodology was designed based on a questionnaire applied through a survey, a file that allowed the collection of information from each of the cows in production and a checklist taken as a reference by MAGAP. The survey revealed that the quantity of liters of milk obtained in most farms is low in relation to Sierra. On the other hand, data were taken for 7 days from each of the cows in order to carry out a statistical analysis, which determined which farm, genetic group and lactation time statistically influences milk production. On the other hand, through the application of a checklist, it was possible to know that all the farms presented non-compliance with the requirements established by good livestock practices in milk production, highlighting 3 aspects as the main problems, the same that served as support for the elaboration of an improvement manual.